Inovasi Pedagogi Bahasa Arab: Tinjauan Pembelajaran Berpusat pada Mahasiswa di Perguruan Tinggi - Fahrur Rosikh (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2026)
This study aims to analyze student-based Arabic language learning innovations at Sunan Drajat University and examine their implementation and impact on the learning process in higher education. The background of this study is based on the need for transformation of Arabic language learning from conventional models to a more active, collaborative, and student-centered approach to improve the quality of 21st-century learning. This study uses a qualitative approach with a case study design. Data were collected through non-participatory observation, in-depth interviews, and documentation. Informants consisted of lecturers, students, and study program managers selected using purposive sampling techniques. Data analysis was carried out using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that 1) learning innovations are implemented through Project-Based Learning, Collaborative Learning, and Problem-Based Learning supported by the use of digital technology. 2) Factors supporting innovation include institutional policies that encourage the development of innovative learning, adaptive curriculum development, and the characteristics of digital native students. Meanwhile, inhibiting factors consist of heterogeneity of student abilities and limited facilities. 3) This innovation has a positive impact on improving students' cognitive abilities, Arabic language skills, learning motivation, and collaborative skills. Furthermore, students become more active, confident, and able to apply Arabic in real-life contexts. This study concludes that student-driven learning innovation is effective in improving the quality of Arabic language learning in higher education, but requires continuous strengthening of facilities and institutional support.